2019
DOI: 10.19173/irrodl.v20i2.4121
|View full text |Cite
|
Sign up to set email alerts
|

Octennial Review (2010-2018) of Literature on M-Learning for Promoting Distributed-Based Medical Education in Sub-Saharan Africa

Abstract: Medical education in Africa is in desperate need of reforms, evident in widespread diseases, and an inability to mobilise and train the required medical workforce to deal with these health issues. However, the exponential rise in the use of mobile technologies due to the spread of the Internet and increased telecommunication networks offer an opportunity for the transformation of medical education and practice through the deployment of mobile devices as a medium for learning and conveying health care services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Twenty-first century education has been inundated with seismic pedagogical shifts due in part to the rapid advances in technology witnessed in the last three decennia, especially as a result of the boom in information and communications technologies (ICTs) such as the Internet (Ditimi and Ayanda, 2013; Musaka, 2015; Yunusa et al , 2019). Such shifts are the result of the use of the Internet and other digital technologies to enhance human learning.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-first century education has been inundated with seismic pedagogical shifts due in part to the rapid advances in technology witnessed in the last three decennia, especially as a result of the boom in information and communications technologies (ICTs) such as the Internet (Ditimi and Ayanda, 2013; Musaka, 2015; Yunusa et al , 2019). Such shifts are the result of the use of the Internet and other digital technologies to enhance human learning.…”
Section: Introductionmentioning
confidence: 99%
“…Given that, there are conflicting positions regarding the low patronage of MOOCs in SSA. Some authors argued that "MOOCs offered on Cousera platforms were more successful among the young, male, well-educated and employed students in developed contexts [17,18].Whereas, Ngimwa and Wilson, [11] reported that low technological level in Africa do not impede the adoption of educational technology, contrary to previous research studies [19][20][21]. Therefore, it is important to dig further to shed more light on the evolution of a disruptive technology such as MOOCs.…”
Section: Introductionmentioning
confidence: 98%
“…However, while most of the countries in the developed contexts have the required infrastructure, workforce, competence and the technology to seamlessly migrate to the alternate, flexible learning medium, not much can be said of countries in the low-middle income bracket of the world particularly in sub-Saharan Africa which are challenged by poor Internet connectivity, inadequate power to drive technology devices and competing budgetary issues [6]. Also, UNICEF and the Microsoft Corporation and the University of Cambridge recently launched "The Learning Passport" a platform for ensuring that students learn even while at home.…”
Section: Introductionmentioning
confidence: 99%